NOVELTIES OF THE RUSSIAN LEGISLATION IN THE FIELD OF DIGITAL CONTENT: CONSOLIDATION OF LEGAL STATUS INFORMATION BROKER - Konobeevskaya Ирина Михайловна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article analyses the problem of intellectual rights protection in information and telecommunication networks.